Zubarev nonequilibrium statistical operator method in Renyi statistics. Reaction-diffusion processes - Kostrobij, P.; Tokarchuk, R.; Tokarchuk, M.; Markiv, B. (Condensed Matter Physics, 2014)
The Zubarev nonequilibrium statistical operator (NSO) method in Renyi statistics is discussed. The solution of q-parametrized Liouville equation within the NSO method is obtained. A statistical approach for a consistent description of reaction-diffusion processes in "gas-adsorbate-metal" system is proposed using the NSO method in Renyi statistics.